ASSESSING THE EFFICIENCY OF UNIVERSITIES' INTERACTION WITH EXTERNAL PARTNERS - Valery M. Zuev; Sergey V. Manakhov; Alla V. Ryzhakova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article shows modern trends in the development of the system of professional education in Russia and identifies the present problems and objectives requiring urgent solutions. According to the authors one objective is the necessity to show the content of the future work and its dynamic changes in the results of learners' training. The authors ground the expediency of designing a new system of links between educational institutions and different agents of external social and economic environment, discuss possible approaches to assessing the efficiency of such interaction and come to the conclusion about the importance of improving the present tools of assessment. General indicators of assessing the efficiency of the present system of partnership were systemized and specific features of their application were identified. Mathematic formulas for calculating the efficiency of partnership were provided for each of the approaches.